Literasi Digital untuk Generasi Muda dan Insan Pendidik Kabupaten Garut yang Lebih Literat - Rohman, Slamet Nopharipaldi; Widyanti, Triani; Suprianto, Dede; Kamila, Azmi Najah (IPI Press, 2025)
Various sectors of life are currently being carried away by the current era of digitalization. Currently, literacy is not only limited to the ability to read and write but is developing towards digital literacy which is an important skill for every individual, including the younger generation and educators in the education sector. This service activity aims to discover strategies for integrating the digital world with education, the main components of integrating digital media with education, and the challenges in integrating digital media with the world of education. This service activity is conducted using an online seminar method for the community. Based on the results of the activities, information was obtained that: 1) implementation of digital media integration strategies with the world of education using appropriate methods and approaches from all parties such as educational institutions, the government, and the students' parents; 2) the main components in integrating digital media with the world of education must be considered and well prepared, starting from technological infrastructure, learning resources and platforms, teacher competency development, curriculum integration, and hybrid learning approaches; and 3) challenges such as unequal access equality, security and privacy in the use of technology, adaptation and resilience in the integration of digital media with the world of education are things that must be faced together so that these challenges will become motivation for all parties to achieve one final goal, namely generation young people and educators who are literate about the digital world in the education sector. Keywords: Digital Literacy, Young Generation, Educators, Education